Research of disaster resistance ability evaluation of mine ventilation system - LIU Yejiao; TIAN Zhichao; LIU Hong; REN Yuhui (Gong-kuang zidonghua, 2015)
The disaster resistance ability evaluation index system of mine ventilation system during fire period was established from five aspects including ventilation system environment, equipments and facilities of ventilation and fire prevention, safety management of ventilation and fire prevention, condition of fire prevention system , and disaster avoidance and relief ability. Then, the weight of each evaluation index was calculated using analytical hierarchy process and the score standard was also made out. Finally, the disaster resistance ability of mine ventilation system during fire period was evaluated through grading method. Theoretical accordance and assurance was provided for improvement and enhancement of reliability, stability and response ability of mine ventilation system during fire period.